How Product Quality, Price, and Service Quality Affect IndiHome Customer Satisfaction - Faris, Riyan Mirdan; Kurniaji, Kalfajrin; Yoedani, Yoedani (West Science Business and Management, 2025)
This study examines the effect of product quality, price, and service quality on IndiHome customer satisfaction in the Datel Cibadak area. Using a quantitative approach, this study involved 68 IndiHome user respondents in the Cibadak area. This study was conducted to what extent product quality, price, and service quality affect customer satisfaction. The instrument used to collect data was a questionnaire that had been tested for validity and reliability. Data analysis was carried out using the Structural Equation Modeling (SEM) technique. The study's results showed that product quality had an insignificant effect on customer satisfaction, indicating that product quality is not the primary factor influencing IndiHome customer satisfaction in this area. Price was also found to have an insignificant effect on customer satisfaction, indicating that price changes do not directly affect their level of satisfaction. Conversely, service quality has a significant impact on customer satisfaction, which means that the service aspect is a key factor in shaping IndiHome customer satisfaction in Cibadak. This study also found that when product quality, price, and service quality are explained simultaneously, all three affect customer satisfaction. This finding has important meaning for Telkomsel company and policymakers in designing more effective strategies to optimize customer satisfaction, especially in the Cibadak area.